2021
DOI: 10.1038/s41598-021-96764-z
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus sequence analysis reveals genetic diversity in Staphylococcus aureus isolate of goat with mastitis persistent after treatment with enrofloxacin

Abstract: Staphylococcus aureus is one of the main bacterial agents responsible for cases of mastitis in ruminants, playing an important role in the persistence and chronicity of diseases treated with antimicrobials. Using the multilocus sequence typing technique, network approaches and study of the population diversity of microorganisms, we performed analyzes of S. aureus (ES-GPM) isolated from goats with persistent mastitis (GPM). The most strains of ES-GPM were categorically different phylogenetically from the others… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…This showed that S. aureus strains with these two spa genotypes were able to both colonize extramammary sites and cause intramammary infections in dairy goats and, therefore, that extramammary sites were frequently colonized with mastitis-associated S. aureus strains. One of the dominant S. aureus spa genotypes found in this herd, t544, is frequently identified in IMI in goats and belongs to the small ruminant-associated clonal complex (CC) 133 [28][29][30][31][32]. Hoekstra et al [28] showed that goat IMI strains with spa genotype t544 have a high production of the leukotoxin LukMF', an important virulence factor for ruminant mastitis.…”
Section: Resultsmentioning
confidence: 99%
“…This showed that S. aureus strains with these two spa genotypes were able to both colonize extramammary sites and cause intramammary infections in dairy goats and, therefore, that extramammary sites were frequently colonized with mastitis-associated S. aureus strains. One of the dominant S. aureus spa genotypes found in this herd, t544, is frequently identified in IMI in goats and belongs to the small ruminant-associated clonal complex (CC) 133 [28][29][30][31][32]. Hoekstra et al [28] showed that goat IMI strains with spa genotype t544 have a high production of the leukotoxin LukMF', an important virulence factor for ruminant mastitis.…”
Section: Resultsmentioning
confidence: 99%